Потребление энергии турбинной ступенью при малорасходных режимах работы - Быстрицкий, Л. Н.; Голощапов, Владимир Николаевич; Касилов, Виктор Иосифович; Козлоков, А. Ю.; Шубенко, Александр Леонидович (НТУ "ХПИ", 2011)
The dependence, which based on results of experimental investigation of turbine stages, for determination of energy consumption at mode of operation lower than idle-running was suggested.
Keywords: номинальный режим работы; вентиляционная потеря; рабочее колесо